2020
DOI: 10.1177/1534735420940394
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Hormone Therapy–Related Side Effects in Breast Cancer Patients: A GRADE-Assessed Systematic Review and Updated Meta-Analysis

Abstract: Purpose: To determine the efficacy of acupuncture on the management of hormone therapy–related side effects in breast cancer patients. Methods: Randomized controlled trials of acupuncture versus a control or placebo in breast cancer patients that examined reductions in therapy-related side effects were retrieved from PubMed, EMBASE, Web of Science, and the Cochrane Library through April 2020. Data on patient symptoms (hot flashes, fatigue, pain, stiffness, and gastrointestinal symptoms), physical capacity, cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 49 publications
0
25
0
1
Order By: Relevance
“… 13 We included 82 publications in this map. 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , …”
Section: Resultsunclassified
See 3 more Smart Citations
“… 13 We included 82 publications in this map. 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , …”
Section: Resultsunclassified
“…The number of studies included for acupuncture in the reviews ranged from 1 to 73 studies. Thirty-seven reviews included fewer than 10 studies, 8 , 9 , 15 , 17 , 18 , 19 , 22 , 23 , 28 , 29 , 30 , 32 , 36 , 41 , 42 , 43 , 45 , 47 , 50 , 52 , 54 , 56 , 61 , 63 , 66 , 68 , 69 , 73 , 79 , 80 , 81 , 82 , 83 , 85 , 90 , 91 , 92 34 reviews included 10 to 25 studies, 14 , 20 , 21 , 25 , 26 , 27 , 29 , 30 , 31 , 33 , 34 , 35 , 37 , 38 , 39 , 40 , 44 , 48 , 51 , 53 , 55 , 58 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the limited e cacy and many side effects of drug therapy, various non-pharmacological techniques have been used in clinical practice [15] . A large number of clinical studies have shown that acupuncture has a de nite effect on enhancing immunode ciency and improving the side effects of adjuvant therapy after radical mastectomy of breast cancer [16][17][18] , and it also shows signi cant advantages in the treatment of chronic urticarial, in ammatory bowel disease and other types of immunode ciency diseases [19][20][21] . The intradermal thumbtack needle, an improved subcutaneous needle, is a type of shallow needling method that reduces pain and prolongs the acupuncture effect via longer needle retention [22] .…”
Section: Introductionmentioning
confidence: 99%